ANALISIS IMPLEMENTASI PROGRAM TERPADU PEMBERDAYAAN MASYARAKAT BERSPEKTIF GENDER DI KOTA SEMARANG - Saleh, Teguh Rahmat; Subowo, Ari; Rostyaningsih, Dewi (Journal of Public Policy and Management Review, 2015)
Implementation of Empowerment programs implemented by the Government of Semarang through the Integrated Program for Community Empowerment Gender-Based (P2MBG) encountered some resistance among communication factors, resources, characteristics of the implementing agency and culture so that the inhibiting factors must be addressed.